Determination of The Best Location Garden of Public Reading (TBM) in Surabaya Using the Method Analysis Overlay and AHP - Dzulfikar Revelation Rosyidi; Rani Purbaningtyas; Fardanto Setyatama (Fakultas Teknik Universitas Bhayangkara, 2020)
The growth of organizations in the field of literacy is very good for the development of children's interest in reading and insight at an early age, especially in the city of Surabaya. Taman Bacaan Masyarakat (TBM) is an organization that has an important role to support and facilitate the community in seeking knowledge in the field of literacy in particular. The addition of TBM in Balai RW, Kelurahan, Kecamatan, and in the corners of community crowds is a tangible manifestation of the role of the Surabaya City Library and Archives Service as the authority that intersects directly in the field of literacy to facilitate the reach of the public in finding quality sources of information. However, several technical factors influence the selection of TBM addition locations that are still very objective. And the limited budget for the establishment of TBM also affects the number of TBM founding locations